Interferon gamma induced-ACSL5 shapes the lipidome of kidney tubular cells - Virginie Poindessous; Julio L. Sampaio; Lydia Bouidghaghen; Ivan Nemazanyy; Alexandre Pallet; Maarten Naesens; Thibaut Vaulet; Dany Anglicheau; Nicolas Pallet (iScience)
Summary: Acyl-CoA synthetase long-chain family (ACSL) enzymes are critical in the activation of long-chain fatty acid. To determine the regulatory mechanisms of ACSL5 and its biological functions within the kidney tubule, we generated transcriptomic, metabolomic, and lipidomic data from experimental models and patient cohorts. We show that ACSL5 is a constituent of a gamma interferon-related gene signature linked to rejection in kidney transplant recipients and the urinary metabolome of kidney transplant recipients who experienced rejection exhibited a deficiency in ACSL5 substrates. We demonstrate that ACSL5 expression is induced in kidney tubular cells in response to IRF-1 signaling, and that it is involved in maintaining ATP production and cell viability and influences their lipid composition, reducing the accumulation of ceramides and the contents in glycerolipids. Thus, modulation of the activity of ACSL5 could impact tubular cell energy metabolism and lipid composition, with a clinical impact in response to kidney allograft injury.